Teaching Metacognitive Reading Strategies: Evidence from Cambodian EFL High School Students - Sophea Pheng; Sarom Mok; Visalboth Pok; Sereyrath Em (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
It is widely considered that students of English as a Foreign Language get a significant advantage by employing metacognitive tactics. Research that has been conducted in the past has led to a greater knowledge of metacognitive reading methods in the English as a Foreign Language environment. Nevertheless, only a small number of studies have found statistically significant effects on students' reading abilities. As a result, this study anticipated an opportunity to clarify this topic by focusing on the proficiency of high school students in Cambodia who are learning English as a foreign language. The purpose of this study is to investigate the effects of metacognitive strategy instruction on students’ knowledge of these strategies and on their reading performance on standardised tests. The study was attended by 55 English as a Foreign Language high school students enrolled in a public school in Phnom Penh, Cambodia. The students participated for a total of eight weeks. The instruments used for the research were the SORS, the English proficiency reading test, and the lesson plans. In comparison to before the instruction, the students in the Cambodian EFL high school employed the PRS the most after the SORS instruction, followed by the GRS and then the SRS. Additionally, it demonstrated significant gains in both approach awareness (p < 0.01) and International English Language Testing System reading scores (M = 6.65 to 8.13, p < 0.01). The usefulness of specific strategy training in improving the reading performance of students studying English as a foreign language is underscored by these findings. In addition, these results will guide educational methods in Cambodia in the future.